Heterocyclic agrochemical hosted by cyclodextrin and hybrid cyclodextrin-silica materials: Characterization, release behavior, and mobility in soil - Bragança Carvalho, Lucas [UNESP]; Abreu Venceslau, Adneia de Fátima; Luz Ambrosio Breisch, Daniela; Fernandes Fraceto, Leonardo [UNESP]; Jaime, Carlos; Matos Alves Pinto, Luciana (Elsevier, 2023)
Atrazine (ATZ) formulations are used to control a broad spectrum of weeds. The combination of ATZ with macromolecular systems, such as cyclodextrins (CDs), can improve its usefulness and herbicide efficacy related to the controlled release of the active ingredient. In this study, inclusion complexes of ATZ in CD and hybrid cyclodextrin-silica materials (CDSI) were prepared and characterized. Infrared spectral analysis of the inclusion compounds, concomitant with the suppression of the endothermic differential scanning calorimetry (DSC) peaks related to the fusion temperature of ATZ, confirmed the inclusion of ATZ in the functionalized and nonfunctionalized oligosaccharides. The linear increase in ATZ solubilization with the increasing addition of CD indicated that the inclusion stoichiometry was 1:1 in all studied systems. The increase in solubilization of the herbicide was approximately 1.3 times for α-CD and γ-CD, which had association constants of 20.3 and 13.4 L mol−1, respectively. The increase in solubility for α-CDSI and γ-CDSI was 3.3 and 2.7-fold, and the association constants were 161.1 and 111.1 L mol−1, respectively. Molecular mechanics (MM) calculations were performed using the force fields MM3* and AMBER*, and the results indicated that the most stable conformations resulted from the penetration of ATZ through the narrower cavity of the CDs. The MD calculations indicated three possible orientations for ATZ in the α-CD cavity, while for γ-CD the amplitude of the standard deviation of the energy values made it impossible to select a more favorable orientation. The ATZ release profile was affected by complexation. Over 22 h, more than 50% of noncomplexed ATZ was released, while for the complexes, less than 20% was released. The complexation, as well as the commercial formulation, provided variations in the development of Brassica juncea seedlings for the layers with higher concentrations of ATZ, thus agreeing with soil layer mobility studies indicated that complexation did not increase the leaching capacity of ATZ, which was mainly distributed in the upper soil layers, where it may be more available for herbicide control functions.
Keywords: Atrazine; Controlled release; Herbicide; Inclusion complex; Soil distribution; Water solubility